ANALYSIS OF THE INFLUENCE OF PRODUCT QUALITY AND SERVICE QUALITY ON CUSTOMER SATISFACTION AT RESTORAN BAKMI KERING HAJI AMAN. - Jimmy Jimmy; Erik Sudarso (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2023)
Competition in the current era of globalization is highly competitive due to changes in people's lifestyles when it comes to food consumption. In the culinary world, one promising field of food is restaurants. There are various types of restaurants or eateries in Singkawang, but what is commonly found are restaurants or eateries serving noodle dishes. The limited number of noodle restaurants presents an opportunity that is capitalized on by Haji Aman's Dry Noodle Restaurant to compete in this field. The objective of this research is to determine whether there is an influence of product quality and service quality on customer satisfaction at Haji Aman's Dry Noodle Restaurant. The research method used is descriptive quantitative, collecting data through questionnaires with a sample of 100 respondents. The research results show that product quality and service quality have a positive impact on customer satisfaction at Haji Aman's Dry Noodle Restaurant.